Monte Carlo calculation of the response of He-3 counter with Geant4 - Manolopoulou, M.; Fragopoulou, M.; Stoulos, S.; Petalas, S.; Zamani, M. (HNPS Advances in Nuclear Physics, 2019)
Monte Carlo calculations with Geant4 were performed to calculate the response of He-3 proportional counters for neutrons of the energy region of 230 keV – 7 MeV. The results are compared with experimental data obtained by irradiation of the detectors with monoenergetic neutron beams produced by 7Li(p,n)7Be and 2H(d,n)3He reactions in the Tandem accelerator, NSCR Demokritos Athens.